2012
DOI: 10.1016/j.bpj.2012.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence Imaging of Living Pancreatic Islets Reveals Fibroblast Growth Factor-21 (FGF21)-Induced Metabolism

Abstract: Fibroblast growth factor-21 (FGF21) has therapeutic potential for metabolic syndrome due to positive effects on fatty acid metabolism in liver and white adipose tissue. FGF21 also improves pancreatic islet survival in excess palmitate; however, much less is known about FGF21-induced metabolism in this tissue. We first confirmed FGF21-dependent activity in islets by identifying expression of the cognate coreceptor Klothoβ, and by measuring a ligand-stimulated decrease in acetyl-CoA carboxylase expression. To fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…The islets of these mice contained a diminished number of beta-cells with reduced glucose sensitivity and impaired insulin processing, demonstrating the importance of FGF signaling in maintenance of beta-cell physiology and glucose homeostasis. We previously confirmed FGFR1 activity in adult murine pancreatic beta-cells, and we further showed changes in islet glucose-stimulated metabolism and insulin secretion in the presence of the FGFR1-ligand FGF21 (2,22). Overall, these data suggest that FGFR1-induced signaling regulates beta-cell biology via classical intracellular signaling responses and may be associated with the onset and progression of metabolic disorders such as diabetes.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…The islets of these mice contained a diminished number of beta-cells with reduced glucose sensitivity and impaired insulin processing, demonstrating the importance of FGF signaling in maintenance of beta-cell physiology and glucose homeostasis. We previously confirmed FGFR1 activity in adult murine pancreatic beta-cells, and we further showed changes in islet glucose-stimulated metabolism and insulin secretion in the presence of the FGFR1-ligand FGF21 (2,22). Overall, these data suggest that FGFR1-induced signaling regulates beta-cell biology via classical intracellular signaling responses and may be associated with the onset and progression of metabolic disorders such as diabetes.…”
supporting
confidence: 71%
“…Pancreatic islets were isolated from 8-to 12-week-old C57BL6 male mice by collagenase digestion (Roche Applied Science) (22). Islets were equilibrated in full RPMI 1640 medium supplemented with 11 mM glucose, 10% FBS, and 5 units/ml penicillin/streptomycin prior to mRNA harvest or dispersion to single cells using Accutase (Sigma) for fixation and immunostaining as described previously (2).…”
Section: Molecular Cloning Of Fgfrl1 and Shp-1 Fluorescent Proteinmentioning
confidence: 99%
“…The mechanism of FGF21 action suggested by this study was via activation of AKT and ERK pathways in beta cells. Another study showed that FGF21 did not affect GSIS from normal mouse islets, but disrupted the potentiating effect of NEFA on GSIS, potentially by altering lipid metabolism and signalling (Sun et al 2012). In addition to a direct effect on beta cells, FGF21 may act indirectly by stimulating secretion of adiponectin from adipocytes (Holland et al 2013;Lin et al 2013) which may in turn stimulate insulin secretion (as reviewed above).…”
Section: Fgf21mentioning
confidence: 95%
“…In adipocytes, FGF21 signals through the fibroblast growth factor receptor 1 (FGFR1) and beta-klotho co-receptor Ogawa et al 2007), and both of these key receptors are expressed in islets (Hart et al 2000;Sun et al 2012). Acute FGF21 administration in mice decreases blood glucose and insulin levels , suggesting a primary role in improving insulin sensitivity.…”
Section: Fgf21mentioning
confidence: 99%
“…Leucine enhanced the mitochondrial fluorescence with no significant effect on the cytosol, while 20 mM glucose roughly doubled the autofluorescence in each compartment. Rocheleau et al (501) attempted to distin-guish changes in matrix NADH from total islet NAD(P)H, by simultaneously monitoring lipoamide dehydrogenase (LipDH) flavin autofluorescence. The enzyme is a component of pyruvate and 2-oxoglutarate dehydrogenases, transferring electrons to NAD ϩ .…”
Section: A Nadph/nadp ؉ Poolsmentioning
confidence: 99%